The evaluation of the use of 2D shear-wave ultrasound elastography in differentiation of clinically insignificant and significant liver fibrosis in pediatric age group. - Akyuz, Melih; Gurcan Kaya, Neslihan; Esendagli, Guldal; Dalgic, Buket; Ozhan Oktar, Suna (Abdominal Radiology, 2021)
Objective: To determine the accuracy of 2D shear-wave elastography (2D-SWE) in pediatric age group patients in differentiating clinically insignificant and significant liver fibrosis using METAVIR fibrosis scoring system as the gold standard. Introduction: Liver biopsy has long been the gold standard in liver fibrosis diagnosis. However, due to probable complications and sampling variabilities, the need for more accurate and non-invasive techniques has increased. 2D-SWE is a non-invasive technique used in the evaluation of liver stiffness and utilized more and more in routine clinical practice with recent advances and researches. Materials and methods: In this retrospective single-center study, we included 46 pediatric age group patients who had a liver parenchymal biopsy and 2D-SWE evaluation regardless of etiology. For 2D-SWE, the LOGIQ E9 system (GE Medical Systems, Wisconsin, USA) and, for histopathological evaluation, METAVIR fibrosis scoring system were utilized. Patients were further subgrouped as clinically insignificant (METAVIR Score F0–1) and significant (METAVIR Score F2–4). The Kolmogorov–Smirnov and Mann–Whitney U tests were employed for statistical analysis. The diagnostic accuracy of 2D-SWE was assessed, and cutoff values were set by ROC curve analysis. Results: kPa values were statistically different between clinically significant and insignificant fibrosis patient groups (p < 0.001). kPa value of 8.92 was designated as the best cutoff value according to the Youden Index. Conclusion: 2D-SWE is one of the non-invasive techniques in the evaluation of liver fibrosis. Our findings suggest that 2D-SWE accurately differentiate clinically insignificant and significant liver fibrosis.